Milímetros da história: memórias e identidades da produção cinematográfica em 16mm em Santa Maria nos anos de 1960 - Daronco, Marilice Amábile Pedrolo (2017)
The present study intends to construct memories about the pioneer cinematographic productions in 16mm in Santa Maria, a town in the central region of Rio Grande do Sul, and analyse how this movies were important for the local cinema. A theme not yet developed by Brazilian film historiography, the first step of our research was to understand the constitution of the amateur filmmaking in 16mm. We make use of the documentary research and Oral History aims to understand and reflect on the cultural context in the 1960s and and its contributions to the film, especially the identity of the santa-mariense cinema. The fiction A ilha misteriosa (1962) and the animated documentary A vida do solo (1968) were the first two cinematographic productions by Santa Maria teams taking into account issues such as narrative, scenarios and esthetics. The documentary was also the first in the world about agroecology. But they were never researched, and memories of these films remained alive only in the memories of people who lived that era and its filmmakers. Through ten interviews as well as the approach to the concepts of authors such as Jöel Candau, Andreas Huyssen and Beatriz Sarlo we discuss the seduction of memory and the duels between remembering and forgetting. Besides that, we invite Aleida Assmann to the discussion with her concept of "mídia da memória", we show how 16mm films constitute an important source of memories about filmmaking in the city, in Rio Grande do Sul and in the country. From this, we were able to point out the six main uses of 16mm and reveal how the support was appropriated by those who wanted to make cinema.